COVID 19-and Oral and Periodontal Manifestation - R. Narayane (Current Overview on Disease and Health Research Vol. 6, 2022)
There has been widespread and recent interest in the variety of COVID-19 symptoms on the oral cavity. Taste disturbances, vague oral ulcerations, desquamative gingivitis, petechiae, and coinfections such candidiasis are some of the oral signs and symptoms of COVID-19. This chapter aims to detail about variety of COVID-19 symptoms on the oral cavity. Transmission of COVID-19 spreads viruses in liquid droplets during speech from covid positive patient. The severity of SARS-CoV-2 infection is higher in middle aged population and in patients with co morbidities. Saliva was observed to be even more sensitive for SARS-CoV-2 detection in COVID-19 patients in comparison to nasopharyngeal swabs. Saliva can have an important role as a diagnostic tool in detection of Covid-19 infection. Even though a link between periodontal findings and the COVID-19 infection can be inferred, more research is required to confirm oral and periodontal presentation as the inaugural symptoms of the COVID-19 infection.